Konservasi Sungai Berbasis Masyarakat (Studi Kasus Kali Garang) - Prabowo, Kholid Zuhud; Setyowati, Dewi Liesnoor (Geo-Image, 2019)
This study aims to determine the characteristics of the Kali Garang river area and determine the forms of conservation that have been running in the community through the use, protection and preservation of river areas. The research method used is descriptive qualitative method. This research was conducted in the Garang Hulu watershed. The sampling technique uses purposive sampling where the sample is taken proportionally by considering the area of the watershed. Research results in the form of diverse characteristics of the Kaligarang region. Water discharge is very much determined by the season. Some V-shaped valleys with steep slopes. The basic material is dominated by large stones, gravel and sand. River conservation is an effort that requires awareness and participation from all parties, both by the community and from the government so that it can create a sustainable and sustainable river.